Fashion industry professionals’ viewpoints on creativity at work - Bukantaitė, Sigita; Sederevičiūtė-Pačiauskienė, Živilė (Creativity Studies, 2021)
The article investigates the attitude of fashion industry managers towards creativity competence and its application in the fashion retail industry. The semi-structured interviews with middle managers allowed distinguishing three categories of activities. In the fashion retail industry, managers need creativity competence: performing technical assignments, working with clients, and working with staff members. For this research, middle managers were chosen because they are the mediators between the company’s general managers and the sales-men. Middle managers play an essential role in bringing organization’s culture, organizing sales-men’s work, and personal development. Therefore, creativity is crucial for managers to have in mind, as the fashion industry is fast changing and dynamic. Creativity competence is effective in a team only if there is proper communication of a manager who can assure all team members understand the organization’s primary purposes and values. The research revealed that managers apply various methods for promoting creativity that includes verbal interactions: discussions, delegating responsibility or tasks, sales promotion games, accumulation and systemization of information, sharing within social networks, provision of feedback, and encouragement of independent search for solutions. This study’s results can help develop job descriptions that would attract the right employees to fashion sales. Understanding the importance of creativity in a salesperson’s day-to-day work can help look at technical or repetitive work differently, increase sales staff’s motivation, and improve sales results.